Perlindungan Hukum Terhadap Hak Hak Masyarakat Desa Dalam Konteks Pemerintahan Desa - Askana Fikriana; Yessy Aulia (Hakim, 2023)
The rights of rural communities are the rights possessed by villagers to participate in the implementation of village government, village development, village community development, and village community empowerment. Legal protection of the rights of rural communities is important to ensure the fulfillment of these rights. In the context of village government, legal protection of the rights of rural communities can be carried out through various means, among others, transparent and accountable village governance. This can be done by opening access to information to rural communities, as well as providing opportunities for villagers to participate in decision making. Law enforcement against violations of the rights of rural communities. This can be done by giving strict sanctions to parties who violate the rights of rural communities. Empowerment of rural communities. This can be done by providing education and training to rural communities and providing access to rural communities to engage in economic activities.